Impacting T-cell fitness in multiple myeloma: potential roles for selinexor and XPO1 inhibitors - Binder, Adam F.; Walker, Christopher J.; Mark, Tomer M.; Baljevic, Muhamed (Frontiers in Immunology, 2023)
Competent T-cells with sufficient levels of fitness combat cancer formation and progression. In multiple myeloma (MM), T-cell exhaustion is caused by several factors including tumor burden, constant immune activation due to chronic disease, age, nutritional status, and certain MM treatments such as alkylating agents and proteasome inhibitors. Many currently used therapies, including bispecific T-cell engagers, anti-CD38 antibodies, proteasome inhibitors, and CART-cells, directly or indirectly depend on the anti-cancer activity of T-cells. Reduced T-cell fitness not only diminishes immune defenses, increasing patient susceptibility to opportunistic infections, but can impact effectiveness MM therapy effectiveness, bringing into focus sequencing strategies that could modulate T-cell fitness and potentially optimize overall benefit and clinical outcomes. Certain targeted agents used to treat MM, such as selective inhibitors of nuclear export (SINE) compounds, have the potential to mitigate T-cell exhaustion. Herein referred to as XPO1 inhibitors, SINE compounds inhibit the nuclear export protein exportin 1 (XPO1), which leads to nuclear retention and activation of tumor suppressor proteins and downregulation of oncoprotein expression. The XPO1 inhibitors selinexor and eltanexor reduced T-cell exhaustion in cell lines and animal models, suggesting their potential role in revitalizating these key effector cells. Additional clinical studies are needed to understand how T-cell fitness is impacted by diseases and therapeutic factors in MM, to potentially facilitate the optimal use of available treatments that depend on, and impact, T-cell function. This review summarizes the importance of T-cell fitness and the potential to optimize treatment using T-cell engaging therapies with a focus on XPO1 inhibitors.